2007
DOI: 10.1007/s00024-007-0194-7
|View full text |Cite
|
Sign up to set email alerts
|

Review of Microgravity Observations at Mt. Etna: A Powerful Tool to Monitor and Study Active Volcanoes

Abstract: Microgravity observations at Mt. Etna have been routinely performed as both discrete (since 1986) and continuous (since 1998) measurements. In addition to describing the methodology for acquiring and reducing gravity data from Mt. Etna, this paper provides a collection of case studies aimed at demonstrating the potential of microgravity to investigate the plumbing system of an active volcano and detect forerunners to paroxysmal volcanic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 38 publications
(39 reference statements)
1
18
0
Order By: Relevance
“…Similar anomalies in the gravity signal were reported, for instance, by Branca et al [2003] and Carbone and Greco [2007], when describing a short-lived explosive event that marked the onset of the 2002 eruption on Etna. In that case, the observed gravity decrease (about À400 μGal) was interpreted as a magmatic intrusion occurring after the development of a fracture system located about 1 km from the gravity station.…”
Section: Gravity Variations During the Eruption Onset 10 To 13 Octobsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar anomalies in the gravity signal were reported, for instance, by Branca et al [2003] and Carbone and Greco [2007], when describing a short-lived explosive event that marked the onset of the 2002 eruption on Etna. In that case, the observed gravity decrease (about À400 μGal) was interpreted as a magmatic intrusion occurring after the development of a fracture system located about 1 km from the gravity station.…”
Section: Gravity Variations During the Eruption Onset 10 To 13 Octobsupporting
confidence: 82%
“…Many studies have confirmed the stability and accuracy of spring-type gravimeters when detecting gravity variations in active volcanic areas and the LaCoste and Romberg and Scintrex gravimeters are the most commonly used [Brown and Rymer, 1991;Budetta and Carbone, 1997;Berrino, 2000;Carbone and Greco, 2007]. In order to study the performances of the meter in terms of resolution, accuracy, noise level, and long-term stability the gPhone-054 used here was compared to the superconducting gravimeter SG-C026 at site J9 in Strasbourg (France) during 2008 [Riccardi et al, 2011].…”
Section: Methodology and Data Acquisitionmentioning
confidence: 99%
“…Meanwhile, Micro‐g LaCoste introduced the commercial Odin leveling platform, which uses the temperature controlled hydraulic legs to correct for tilts with a subarcsecond resolution (Scintrex Ltd, ). It is also possible to compensate tilts affecting LaCoste and Romberg instruments by applying a posteriori a correction computed from electronic levels data (Carbone & Greco, ).…”
Section: Measuring Gravitymentioning
confidence: 99%
“…Continuous high-quality gravity measurements at volcanoes -in combination with geodetic ground deformation and seismic observations -may enable detection of subsurface mass redistribution long before other eruption precursors appear (Carbone and Poland, 2012;Carbone et al, , 2008Rymer and Locke, 1995). Etna in the framework of a scientific project managed by INGV; for a comprehensive review of Etna gravity, see Carbone and Greco (2007). For this reason, several groups in Europe, Mexico, and South America are interested in iSGs for volcano monitoring.…”
Section: Future Possibilitiesmentioning
confidence: 99%